Orthodox and protestant Chinese dictionaries of the 19th – early 20th centuries - Anna Sergeevna Koroleva, Sofiya Andreevna Silakova, Alisa Maratovna Bessonova, (Opción, 2019)
This article is devoted to the experience of compiling English-Chinese and Russian-Chinese dictionaries by representatives of Christian missions working in China in the 19th and early 20th centuries via comparative qualitative research methods. As a result, missionaries made the Chinese language not only more accessible for a foreigner, but also undertook attempts of the decision of the problems of Chinese lexicography. In conclusion, distinctions are traced in the author’s lexicographic conceptions what was reflected in the submission of a lexical material, in the receptions of lexicographic descriptions, in volume and nature of encyclopedic information.